Treatment of Pre-treated Textile Wastewater using Moving Bed Bio-film Reactor. (2016) - Francis, Anju; Sosamony, K.J.
Abstract: Control of water pollution is a very important scientific research area nowadays. Textile industry is one among the major pollution causing industry. The organic compounds which are coloured represent a minor fraction of the organic components of wastewater but their colour causes undesirable appearance. Treatment of textile wastewater using traditional physico-chemical methods are expensive, large quantities of sludge will be generated and usually it needs the addition of toxic chemicals. Textile effluents have high COD and low BOD. So it is not suitable to treat textile wastewater using a single physico-chemical or biological method. So a chemical pre-treatment followed by biological treatment is suitable for textile wastewater. Advanced oxidation process is chosen for pre-treatment. Among various advanced oxidation processes, fluidized bed Fenton process is chosen because sludge produced is less in this process. The efficiency of MBBR with carriers inoculated with Microbacterium marinilacus, isolated from textile sludge after fluidized bed Fenton pre-treatment is evaluated. Results are optimized using Box Behnken method. 86% COD removal, 81.5% BOD removal is observed.